First figure the distance between the two points:
d = sqrt(Δx² + Δy²)
Δx = x1 - x2 = 6 - 1 = 5
Δy = y1 - y2 = -5 - 7 = -12
d = sqrt(5² + (-12)²)
d = sqrt(25 + 144)
d = sqrt(169)
d = 13
When you have a point (x1, y1) as the center and r as a radius, the general formula for a circle is:
(x - x1)² + (y - y1)² = r²
So using your values of:
x1 = 6
x2 = -5
r = 13
(x - 6)² + (y - (-5))² = 13²
This simplifies to:
(x - 6)² + (y + 5)² = 169
2006-12-14 11:02:03
·
answer #1
·
answered by Puzzling 7
·
2⤊
0⤋
First, the equation for a circle is (x - h)^2 + (y - k)^2 = r^2, where the center of the circle is the point (h,k) and r is the radius.
That gives us (x-6)^2 + (y+5)^2 = r^2.
So, we have to determine the radius. We know the center point, and we have one point in the circle. If we graph those point on graph paper, we can construct a right triangle with the line connecting those 2 points as our hypotenuse. The base of that triangle would be 5 and the height would be 12. Using the rules we know about right triangles, also known as the Pythagorean Theorem, we've got 5^2 + 12^2 = c^2, c being our hypotenuse. 25 + 144 = c^2, or 169 = c^2, giving us c = 13. That's our radius.
So, the equation for this circle is (x-6)^2 + (y =5)^2 = 169
2006-12-14 19:12:37
·
answer #2
·
answered by HappyHeather 2
·
1⤊
0⤋
The general equation of a circle is
(x-xc)^2 + (y-yc)^2 = r^2
where (xc, yc) is the center of the circle and r is the radius.
So you already know the center. The radius can be found by plugging the point on the circle into the equation and solving for r
2006-12-14 19:02:16
·
answer #3
·
answered by rscanner 6
·
1⤊
0⤋
(x - 6)^2 + (y + 5)^2 = 169
2006-12-14 19:00:59
·
answer #4
·
answered by Northstar 7
·
1⤊
0⤋
(x-6)^2 + (y+5)^2 = 169
2006-12-14 19:01:04
·
answer #5
·
answered by Jose N 2
·
1⤊
0⤋
(x-x1)^2+(y-y1)^2=r^2
(x-6)^2+(y-(-5))^2=r^2
(x-6)^2+(y+5)^2=r^2
r^2=(y2-y1)^2+(x2-x1)
r^2=(7+5)^2+(1-6)^2
r^2=12^2+5^2
r^2=144+25=169
Here's the answer:
(x-6)^2+(y+5)^2=169
2006-12-14 19:19:20
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋